Combined Institutional and Telerehabilitation Programs for A Post-Tuberculosis Lung Disease Patient with Low Cardiorespiratory Endurance: A Case Report - Widjanantie, Siti Chandra; Agustin, Heidy; Handayani, Diah; Burhan, Erlina; Susanto, Agus Dwi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Post-tuberculosis lung disease (PTLD) can lead to long-term respiratory issues and impaired lung function, which can impact quality of life. Pulmonary rehabilitation (PR) is a personalized strategy designed to address these problems and improve overall well-being. It is administered by a diverse team of experts. Case: A 28-year-old female patient with a history of tuberculosis (TB) presented with breathing difficulty. The physical examination revealed decreased chest expansion, shoulder asymmetry, a slight forward neck, and a rounded shoulder. The radiologic findings and bronchoscopy showed PTLD, atelectasis in several parts of the right lung, and regional destruction of the right lung. Discussion: The patient underwent pulmonary rehabilitation (PR), which included endurance exercises, strength training, several types of breathing exercises, breath-stacking exercises, thoracic expansion exercises, physical agents for rehabilitation modalities, education on posture correction, and energy conservation in daily activities. The patient was also monitored remotely through telerehabilitation from home. There were significant improvements in pulmonary function tests. Measurement of FVC, FEV1, the six-minute walking test (6MWT), and the PCF after two weeks of follow-up. After eight weeks of training, there were improvements in cardiopulmonary endurance, muscle endurance, and reduced dyspnea. Conclusion: Comprehensive pulmonary rehabilitation programs, including a combination of institutional and telerehabilitation synchronous approaches, can help improve cardiopulmonary endurance, muscle strength-endurance, and the overall patient's functional life who was suffering from chronic respiratory diseases, such as post-TB sequelae.